2020
DOI: 10.1177/2325967120954430
|View full text |Cite
|
Sign up to set email alerts
|

Small, Short, Oblique Patellar Tunnels for Patellar Fixation Do Not Increase Fracture Risk or Complications in MPFL Reconstruction: A Retrospective Cohort Study

Abstract: Background: Large (4.5 mm) and/or transpatellar bone tunnels have been associated with patellar fracture after medial patellofemoral ligament (MPFL) reconstruction. To avoid this outcome, many surgeons now employ suture anchors to affix the MPFL graft to the patella. Purpose: To evaluate the risk of patellar fracture and other outcomes associated with smaller (3.2-mm), short, oblique patellar tunnels as compared with suture anchor fixation in MPFL reconstruction. Study Design: Cohort study; Level of evidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Other advantages of small, oblique patellar tunnels with looped graft possibly include enhanced graft-to-bone healing by providing a larger area of graft to bone contact and increased cost effectiveness relative to the suture anchor fixation technique. 8 In conclusion, the use of small (3.2-mm), short, oblique patellar tunnels with looped graft is safe, efficacious, and cost-conscious and should be considered a viable option for patellar fixation during MPFL reconstruction.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Other advantages of small, oblique patellar tunnels with looped graft possibly include enhanced graft-to-bone healing by providing a larger area of graft to bone contact and increased cost effectiveness relative to the suture anchor fixation technique. 8 In conclusion, the use of small (3.2-mm), short, oblique patellar tunnels with looped graft is safe, efficacious, and cost-conscious and should be considered a viable option for patellar fixation during MPFL reconstruction.…”
Section: Discussionmentioning
confidence: 87%
“…7 A recent retrospective cohort study by Deasey et al including 384 knees in 354 patients undergoing MPFL reconstruction presented outcomes with the use of smaller (3.2-mm), short, oblique patellar tunnels for graft fixation. 8 Importantly, they found that the use of smaller tunnels was not associated with an increased incidence of patellar fracture compared with the use of suture anchors. Additionally, they reported only one instance of patellar fracture out of a cohort of 215 knees (incidence 0.46%), which is lower than the historical rates presented in similarly sized studies by Schipouwer et al 5 and Parikh et al 6,8 Deasey et al 8 also showed that the use of these small (3.2-mm), short, oblique tunnels led to a statistically significant decrease in the risk of recurrent patellar instability events compared with suture anchors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This study highlights the associated, increased risk seen with the use of transverse patellar bone tunnel while performing MPFL reconstruction. Recently, Deasey et al [161] have shown that the use of small-diameter (3.2-mm), oblique patellar bone tunnels was not associated with an increased risk of patellar fracture in comparison with the use of suture anchors for patellar fixation. Deasey et al [161] concluded that the use of small (3.2-mm), short, oblique patellar tunnels can be a safe and reliable method of patellar graft fixation in MPFL reconstruction.…”
Section: Discussionmentioning
confidence: 99%